Advanced technologies used in local government units on the example of the commune of Zabór in years 2018-2022 (Discourse of Law and Administration, 2025)
The technological advancement and development of our civilization in the 21st century has resulted in significant changes in our life. Changes in, for instance, information and communication technology are apparent in every area of life, including administration. The implementation of advanced technologies and adjusting them to the changing environment has a large impact on the operations of local government units, which I have presented based on the example of the commune of Zabór. In this article, I have discussed many theoretical and practical aspects of the application of new technologies in the commune of Zabór.
Keywords: electronic signature; electronic registers; commune of Zabór; ePUAP; advanced technologies; computerization